Law No. 9 of the Year 2024 On Expediting the date of Entitlement to the periodic Raises, Granting a Special Raise To the Workers Non-Addressed by the Civil Service Law, Increasing the Additional Incentive Payable to the State Civil Servants, Giving a Special Grant to the Workers of the Public Sector Companies and Public Business Sector Companies, And Increasing the Civil and Military Pensions = قانون رقم 9 لسنة 2024 بتعجيل موعد استحقاق العلاوات الدورية ومنح علاوة خاصة لغير المخاطبين بقانون الخدمة المدنية وزيادة الحافز الإضافى للعاملين بالدولة وبتقرير منحة خاصة للعاملين بشركات القطاع العام وقطاع الاعمال العام وزيادة المعاشات المدنية والعسكرية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic